Perancangan Sistem Informasi Rapor Siswa SKB Dinas Pendidikan Kabupaten Asahan - Hana Kamilia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to facilitate the process of processing grades for teachers in the SKB field of the Education Service. Managing student data and information is a very important aspect to support an effective teaching and learning process. One form of crucial data management is the student report card information system. For the problems above, a report card processing application is needed that can make reporting easier by creating a reintegrative data processing information system. This research was conducted using qualitative methods with data collection in this research using observation, interview and documentation techniques. By designing this information system, it can be a solution and meet the needs of problems in processing report cards manually, so that the grades managed become easier and faster.